Efectos de los filtros de absorción de luz azul a nivel ocular (2021)
At present, the population faces constant exposure to blue light emitted by electronic devices for long periods of time, this type of light generates damage and alterations in the visual system and the circadian rhythm. Objective: Identify the effects of blue light absorption filters at the ocular level. Methodology: A narrative review was carried out in Science Direct, PubMed and Google Academic of articles in English and Spanish, and academic texts between 2010 and 2020. Results: A total of 70 articles were evaluated, 31 were included for meeting the criteria inclusion. Turquoise blue light was found to be beneficial for eye development, while violet blue light is detrimental to eye health, and blue light absorbing filters are a good way to counteract these effects. Conclusions: The indicated filters reduce visual fatigue, contribute to visual effectiveness, comfort and quality, reduce or eliminate itching, eye irritation and tearing.